Stomatitis sub-prosthesis in patients with superior dental prosthesis - Antonia Martina Francisco Local; Yoel González Beriau; Ana Gloria Vázquez de León (Medisur)
Background: The stomatitis sub-prosthesis is one of the most frequent changes in hard palate mucous membrane in patients with mucous-supported dental prosthesis. It can be caused by multiple factors, which makes its study and prognosis more difficult. Objective: To describe the occurrence of stomatitis sub-prosthesis and its causes in patients with superior dental prosthesis. Method: Descriptive study including all the patients with superior dental prosthesis examined in the odontology consultation “Barrio Adentro” in the state of Miranda, Venezuela, from November, 2005 to March, 2006. The analysed variables were: age, sex, stomatitis level, teeth brushing frequency, prosthesis condition and use, palate mucous condition and frequency of odontology consultations. Results: 89 patients were attended, more 50% of them had superior dental prosthesis and presented stomatitis sub-prosthesis; the group between 35 and 59 years was the most affected, mainly females. Sub-prosthesis stomatitis type II was the most common and the main causes included constant use of the prosthesis and loose prosthesis. Buccal hygiene was not adequate in these patients. Most of them declared never attending to the dentist, or just when presenting some particular problem. Conclusion: Stomatitis prevalence was related with incorrect hygiene habits and lack of knowledge; it shows the importance of performing educative tasks to reduce this disease incidence.